Fenretinide causes emphysema, which is prevented by sphingosine 1-phoshate. - Masanori Yasuo; Shiro Mizuno; Jeremy Allegood; Donatas Kraskauskas; Harm J Bogaard; Sarah Spiegel; Norbert F Voelkel (PLoS ONE)
Sphingolipids play a role in the development of emphysema and ceramide levels are increased in experimental models of emphysema; however, the mechanisms of ceramide-related pulmonary emphysema are not fully understood. Here we examine mechanisms of ceramide-induced pulmonary emphysema. Male Sprague-Dawley rats were treated with fenretinide (20 mg/kg BW), a synthetic derivative of retinoic acid that causes the formation of ceramide, and we postulated that the effects of fenretinide could be offset by administering sphingosine 1-phosphate (S1P) (100 µg/kg BW). Lung tissues were analyzed and mean alveolar airspace area, total length of the alveolar perimeter and the number of caspase-3 positive cells were measured. Hypoxia-inducible factor alpha (HIF-1α), vascular endothelial growth factor (VEGF) and other related proteins were analyzed by Western blot analysis. Immunohistochemical analysis of HIF-1α was also performed. Ceramide, dihydroceramide, S1P, and dihydro-S1P were measured by mass spectrometer. Chronic intraperitoneal injection of fenretinide increased the alveolar airspace surface area and increased the number of caspase-3 positive cells in rat lungs. Fenretinide also suppressed HIF-1α and VEGF protein expression in rat lungs. Concomitant injection of S1P prevented the decrease in the expression of HIF-1α, VEGF, histone deacetylase 2 (HDAC2), and nuclear factor (erythroid-derived 2)-like 2 (Nrf2) protein expression in the lungs. S1P injection also increased phosphorylated sphingosine kinase 1. Dihydroceramide was significantly increased by fenretinide injection and S1P treatment prevented the increase in dihydroceramide levels in rat lungs. These data support the concept that increased de novo ceramide production causes alveolar septal cell apoptosis and causes emphysema via suppressing HIF-1α. Concomitant treatment with S1P normalizes the ceramide-S1P balance in the rat lungs and increases HIF-1α protein expression via activation of sphingosine kinase 1; as a consequence, S1P salvages fenretinide induced emphysema in rat lungs.